Functional and Clinical Outcomes of Combined Simultaneous Bilateral Anterior Distal Femoral Plate Hemiepiphysiodesis and Hamstrings Release in Management of Knee Flexion Contractures in Children With Neuromuscular Disorders. Issue 9 (October 2021) - Zaghloul, Ahmed; Manoukian, Dimitrios; Barrett, Matthew C.; Geronta, Ilektra; Maizen, Claudia
Abstract : Background: We examined the clinical and functional outcomes of the simultaneous anterior distal femoral 8-plate hemiepiphysiodesis (ADF8PH) and hamstring release, for fixed knee flexion deformity in children with neuromuscular disease. To our knowledge, no published evidence is available that reports the outcomes of this combined techniques. Methods: Electronic medical records were retrospectively reviewed for 19 consecutive children who underwent bilateral ADF8PH and concomitant hamstrings release in our institution from 2012 to 2019. Relevant demographics, Gross Motor Functional Classification Score and preoperative and postoperative knee flexion contractures and popliteal angles were documented. Results: The average age at the time of operation was 12±2.1 years. There were 15 males and 4 females. Diagnoses included cerebral palsy (n=16), Cornelia de Lange syndrome (n=1), hereditary spastic paraplegia type 56 (n=1) and fructose-1, 6 bisphosphonate aldose B deficiency (n=1). Mean length of follow-up was 3.8 years (range: 1.5 to 7 y). Mean fixed knee flexion deformity improved from 28.9 to 13.4 degrees ( P <0.001) at an average correction rate of 0.94 degrees per month. Mean popliteal angle improved from 81.8 to 44.4 degrees ( P <0.001) in the early postoperative phase and to 51.8 degrees ( P <0.001) in latest clinic review. Mean time to correction was 18.9 months. The agreed treatment goals of maintaining or promoting the use of standing frame and spinal/postural symmetry was attained in 18 patients (94.7%). Postoperative knee pain was reported in 2 cases (10.5%). We report 2 complications; 1 case of neurapraxia and 1 case of sepsis because of respiratory infection. Conclusion: Simultaneous bilateral ADF8PH with hamstrings release is a promising effective technique for correction of knee flexion contractures in skeletally immature individuals with neuromuscular disabilities. Our findings demonstrate improvement in clinical outcomes and maintaining functional outcomes, indicating the validity of this approach as a satisfactory, less invasive alternative in the management of this deformity. Level of Evidence: Level IV—therapeutic study.